ANTIOXIDANT ACTIVITY OF NIRA SEED WASTE (ARENGA PINNATA) EXTRACTS USING DPPH METHOD - Wiwit Zuriati Uno; Rifka Anggraini; Anggi Pratama Solihin; Juliyanti Akuba (JIMR : Journal Of International Multidisciplinary Research, 2025)
Agricultural waste from Nira (Arenga pinnata) seeds has attracted increasing attention due to its potential bioactive compounds and value-added applications. Objective: This study aims to evaluate the antioxidant activity of nira seed waste (Arenga pinnata) using solvents with different polarity levels. Method: The research employed an experimental laboratory method with maceration extraction using ethanol, acetone, and n-hexane. Antioxidant activity was analyzed using the DPPH radical scavenging assay measured by UV–Vis spectrophotometry. Results: The results showed that solvent polarity influenced extraction yield, phytochemical composition, and antioxidant potential. The ethanol extract exhibited the strongest antioxidant activity due to its effectiveness in extracting phenolic and flavonoid compounds. These findings indicate that nira seed waste has promising potential as a natural antioxidant source and pharmaceutical raw material supporting the zero waste concept.